Evaluation of level of satisfaction among indoor patients attending in a tertiary care hospital of Rajnandgaon (C.G.), India - Verma, Nirmal; Kamble, Nitin; Bhawnani, Dhiraj; Makade, Kiran; Dengani, Monika; Kaushik, Tarun (International Journal Of Community Medicine And Public Health, 2018)
Background: Patient expression is an important source of information in screening for problems and developing an effective plan of action for quality improvement in health care organizations. Assessing satisfaction has been mandatory for quality control of any hospital, which has resulted in an increasing number of projects devoted to the concept of satisfaction and determinant of patient satisfaction. Methods: The present Cross sectional Observational Hospital based study was conducted in Government Medical College Hospital, Rajnandgaon (C.G.) India during April 2016 to September 2016. A sample of 200 patients was taken who were admitted in different Indoor Patients Department of Clinical departments. Patients were selected according to inclusion and exclusion criteria. The information from the patients on various aspects of patient’s satisfaction like admission procedure, communication with staff, physical care, test and operation help availability, cleanliness, privacy related issues and overall satisfaction was obtained by interview with patients based on the semi structured questionnaire proforma. Results: In the present study, among IPD patient Male: Female ratio was 3:2 approx. Helpfulness of person at registration desk was ranked very good by 93% subject. Wheelchair was available for most of the patients (95%) but its availability when needed was ranked very good by 76% patients only. Majority of patient were satisfied with the behavior of the lab technician (89%), availability of lab results on given time (81%). Conclusions: This study shows that patients admitted in the various wards of hospital were satisfied with the quality of professional services by doctors, nursing and paramedical staff but problem lies with the availability of basic amenities. Overall present study shows that assessing satisfaction of patients is simple, easy and cost effective way for evaluating the hospital services.